Advanced material characterization techniques for sodium‐ion battery. Issue 4 (18th June 2022) - Liu, Xiangyu; Tong, Shuai; Zhang, Xiaoyu; Jia, Min; Yan, Xiaohong
Abstract: Sodium‐ion batteries, which are viewed as the alternative candidate for lithium‐ion batteries, are now receiving extensive attention in recent years. This is because of the earth's abundance, the widespread sodium resource, and the low cost of battery production. Despite tremendous effort has been made to improve the battery performance of sodium‐ion batteries, several serious problems hinder the large‐scale practical applications. These problems such as low energy density and efficiency, poor cycle life, and low charge/discharge rate are largely determined by fundamental mechanism issues of electrode materials that are not sufficiently understood yet. Therefore multiple techniques should be used to get an in‐depth understanding of material properties. In this review, a comprehensive overview of the material characterization technique is provided and hope it could improve the battery research for all the scientific researchers.